Experiences of post-matriculants regarding basic schooling and education in Cape Town – South Africa: qualitative study with post matriculants in Du Noon township - Frydie, Asheeqah (Department of Social Development, 2025)
This qualitative, explorative research study aimed to explore post-matriculant experiences about accessing jobs in South Africa. The study explored experiences about accessing jobs concerning the ease or difficulty of finding jobs for post-matriculants. In addition, the study explored those who found it easier to find such jobs based on what they went through. For those who found it hard to find jobs, the research explored reasons they found it challenging. Finally, factors attributed to finding it easier or difficult to access jobs and what can be done to make it easier for post-matriculants to find jobs were interrogated. This study used an exploratory and qualitative research design whereby 15 participants were recruited using purposive non-probability sampling. Face-to-face interviews were used in data collection. Significant findings of the research investigation concerned the post-matriculants having various experiences accessing jobs, as some found them more accessible. In contrast, others found it very difficult to access jobs. A few post-matriculants indicated they found it easier to access jobs because they had gone through tertiary education. At the same time, many of them stated that they faced challenges in accessing jobs as they had only matriculant certificates, societal pressure to succeed, mental and emotional health concerns, and a lack of necessary skills to enter the labour market. One significant implication of the research findings is that the curriculum was not properly equipping post-matriculants with the skills to successfully enter the labour market upon completion of their matriculation, hence the high unemployment rates. In conclusion, post-matriculants need various interventions after matriculation to access tertiary education and relevant vocational training and have a curriculum appropriately formulated to equip them with the skills to enter the labour market successfully. Since this research has shown that the more significant number of the people interviewed indicated that it was difficult to access jobs, it is recommended to conduct further research to make it easier for post-matriculants to find jobs. It is further recommended that policymakers be more mindful of post-matriculants' challenges and implement initiatives to ease their transition from school to the labour market.